2018
DOI: 10.1039/c8ta06391e
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cesium on the phase and device stability of triple cation Pb–Sn double halide perovskite films and solar cells

Abstract: Csx(MA0.17FA0.83)1−xPb1−ySny(I0.83Br0.17)3 perovskites with cubic-phase morphologies were deployed in solar cells, achieving high efficiencies and improved stability for high Sn-containing devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 54 publications
0
32
0
Order By: Relevance
“…If we consider Cs + , that is the nonradioactive element with the largest ionic radius, the tolerance is comprised between 0.85 and 0.88, as shown in Table 1 for every combination of B and X. For this reason, CsBX 3 perovskites are not stable in the cubic black‐phase (bandgap 1.73 eV) at ambient temperature and tend to transform into orthorhombic perovskite characterized by the yellow color and a larger bandgap (>3 eV) . For this reason, Cs is usually substituted by MA and FA that lead to optimal tolerance factor values (see Table ).…”
Section: Lead‐free Alternativesmentioning
confidence: 99%
“…If we consider Cs + , that is the nonradioactive element with the largest ionic radius, the tolerance is comprised between 0.85 and 0.88, as shown in Table 1 for every combination of B and X. For this reason, CsBX 3 perovskites are not stable in the cubic black‐phase (bandgap 1.73 eV) at ambient temperature and tend to transform into orthorhombic perovskite characterized by the yellow color and a larger bandgap (>3 eV) . For this reason, Cs is usually substituted by MA and FA that lead to optimal tolerance factor values (see Table ).…”
Section: Lead‐free Alternativesmentioning
confidence: 99%
“…For the FAPbI 3 perovskite film, the diffraction intensity along (001) direction was substantially increased in most case, as a result of its cubic phase. With respect to MA/FA mixed perovskites, a preferred orientation along (100) and excellent crystallinity were obtained through Sn doping, Br doping, or the templating effect associated to the specific beneath layer . Besides, a preferred orientation along (021) or (012) in mixed FA/MA perovskite film could be achieved by altering organic cation concentration, or meniscus‐assisted solution printing strategy .…”
mentioning
confidence: 99%
“…In our previous work, we showed that the band gap of Cs x (MA 0.17 FA 0.83 ) 1Àx Sn(I 0.83 Br 0.17 ) 3 perovskites decreases with decreasing lattice parameter due to a smaller average cation radius. 33 Both A-site induced BX 6 octahedral tilting and B-X overlap on the conduction and valence band edges of perovskites influence these band gap trends. 34 The correlation between the band gap decrease and the lattice parameter decrease for (CsGA) x without EDAI 2 reflects that the same mechanism is occurring, where the increased isotropic lattice constrictions and B-X overlap make the valence band maximum shift upwards more than the conduction band minimum.…”
Section: Resultsmentioning
confidence: 99%